Examining the Backlash Against Women Who Confront Sexism and the Role of Evolving Gender Expectations - Akhtar, Muna (Tufts University Tisch Library, 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Psychology.; Advisor: Keith Maddox.; Committee: Amanda Diekman, Samuel Sommers, Ayanna Thomas, and Heather Urry.; Keyword: Social psychology